Prescribing pattern of drugs in the outpatient department of a tertiary care teaching hospital in Ghaziabad, Uttar Pradesh - Goel RK, Bhati Y, Dutt HK and Chopra VS (Journal of Applied Pharmaceutical Science, 2013)
The study was done to find out the current prescribing pattern in this tertiary care teaching hospital in Ghaziabad. The study was carried out at Santosh Medical College and Hospital over a period of 3 months. A total of 500 prescriptions were collected and analyzed. Total number of drugs prescribed was 1450 out of which 564 drugs were prescribed by generic names. Average number of drugs was 2.9. 327 drugs were fixed dose combinations while only 595 were from essential drug list. The mean number of drugs per prescription should be as low as possible otherwise there is increase risk of drug interaction, bacterial resistance, non-compliance and increase in cost The prescribing practices are more of irrational types like polypharmacy, use of vitamins and injections, less number of drugs by generic names and lesser drugs from Essential Drug List. There is an urgent need for some interventions to improve the situation.
Keywords: Prescription, Rational, Fixed Dose Combination, Esse